Two-chambered water-filled geomembrane tubes used as water barriers: experiments and analysis. Issue 3 (May 2005) - Kim, M.; Filz, G. M.; Plaut, R. H.
Abstract : Geomembrane tubes are used to withstand external water in various applications, such as flood control, diversion or impoundment of water, and dewatering work sites (i.e. as cofferdams). The external lateral pressure must be resisted, so that the tube does not roll or slip along the ground. Two techniques involving multi-chambered tubes are examined here. In one, the tube has a perforated internal baffle (diaphragm) to resist deformation and rolling. In the other, two tubes are surrounded by an outer tube (sleeve), and friction between the components helps to stabilize the structure. Experiments are conducted on the latter case, and numerical analysis using the finite difference program FLAC is applied to both cases. Various geometrical and friction properties, internal pressures, and headwater levels are considered. Deflected shapes, tensions, critical headwater levels, and corresponding failure modes are determined. The effects of several parameters are investigated. In the examples treated, the critical headwater levels range up to 90% of the height of the baffle tube and up to 80% of the height of the sleeved dam. These devices can be effective fluid barriers (e.g. in place of sandbags for flood protection) if the headwater levels are not too high.